2022
DOI: 10.1128/mbio.00687-22
|View full text |Cite
|
Sign up to set email alerts
|

Listeria-Vectored Multiantigenic Tuberculosis Vaccine Enhances Protective Immunity against Aerosol Challenge with Virulent Mycobacterium tuberculosis in BCG-Immunized C57BL/6 and BALB/c Mice

Abstract: TB, one of the world's most important infectious diseases, afflicts approximately 10 million people and kills approximately 1.5 million people annually. The current vaccine, BCG, developed over a century ago, has been administered to about 5 billion people, mostly in infancy, but is only modestly protective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…Construction and verification of rLm9Ag expressing fusion proteins of Mtb5Ag and Mtb5AgII from the comK and tRNA arg loci, respectively. To construct rLm5Ag (expressing Mtb Mpt64-EsxH-EsxA-EsxB-r30, with an N-terminal fusion to ActAN, the N-terminal 100 amino acids of Lm ActA) 23 (Supplementary Table 1) and rLm5AgII (expressing ActAN-Mpt64-EsxN-PPE68-EspA-TB8.4) (Supplementary Table 1), we integrated the pPL2e-ActAN-Mtb5Ag and pPL2e-ActAN-Mtb5AgII into the tRNA arg locus of the rLm chromosome (Fig. 1a, top and middle vaccines).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Construction and verification of rLm9Ag expressing fusion proteins of Mtb5Ag and Mtb5AgII from the comK and tRNA arg loci, respectively. To construct rLm5Ag (expressing Mtb Mpt64-EsxH-EsxA-EsxB-r30, with an N-terminal fusion to ActAN, the N-terminal 100 amino acids of Lm ActA) 23 (Supplementary Table 1) and rLm5AgII (expressing ActAN-Mpt64-EsxN-PPE68-EspA-TB8.4) (Supplementary Table 1), we integrated the pPL2e-ActAN-Mtb5Ag and pPL2e-ActAN-Mtb5AgII into the tRNA arg locus of the rLm chromosome (Fig. 1a, top and middle vaccines).…”
Section: Resultsmentioning
confidence: 99%
“…Prime vaccines under development, all comprising mycobacteria, include rBCG30, the first vaccine demonstrated more potent than BCG and the first potential replacement vaccine for BCG to enter human trials [4][5][6][7] ; rBCG(mbtB)30, the first vaccine demonstrated more potent and safer than BCG 8 ; MTBVAC, an attenuated Mtb 9 , and VPM-1002, a modified BCG 10 . TB booster vaccines under development, all subunit vaccines, include protein/adjuvant vaccines such as r30 (Antigen 85B), the first defined booster vaccine against TB 4 , H1 (Antigen 85B -ESAT6) 11,12 , H4 (Antigen 85B-TB10.4) 13,14 , M72 15,16 , and ID93 17,18 ; virus vectored vaccines such as MVA85A 19,20 ; and bacterium vectored vaccines including Salmonella-vectored vaccines 21 and Listeria-vectored vaccines, including rLm30 22 and rLmMtb5Ag 23 , as well as rLmMtb9Ag, described herein.…”
mentioning
confidence: 99%
See 3 more Smart Citations